2015
DOI: 10.1108/ijppm-12-2013-0205
|View full text |Cite
|
Sign up to set email alerts
|

Logistics firms performance: efficiency and effectiveness perspectives

Abstract: Purpose – The purpose of this paper is to assess the efficiency, effectiveness and performance of logistics companies in Singapore and Malaysia which are the growing logistics hubs in Asia by using a triangular data envelopment analysis (DEA). It also identifies various factors that significantly affect the efficiency, effectiveness and performance of the Singaporean and Malaysian logistics companies and proposes ways to improve their competitiveness. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…All three proposed relationships were statistically significant. The findings did not only reveal the importance of logistics activities in achieving high levels of competitive advantage, but also revealed how the positioning of SMEs logistics activities is centered around quality − doing things right; speed − doing things fast; delivery dependability − doing things on time; and flexibility − changing what you do and the cost of doing things cheaply (Wong, Soh, Chong, Karia, 2015;Taschner, 2016;Aharonovitz, Vieira, Suyama, 2018;Omoruyi, 2018). To survive the fast-changing business environment, logistics activities are critical business tools to obtaining a competitive advantage.…”
Section: Conclusion and Managerial Implicationmentioning
confidence: 99%
“…All three proposed relationships were statistically significant. The findings did not only reveal the importance of logistics activities in achieving high levels of competitive advantage, but also revealed how the positioning of SMEs logistics activities is centered around quality − doing things right; speed − doing things fast; delivery dependability − doing things on time; and flexibility − changing what you do and the cost of doing things cheaply (Wong, Soh, Chong, Karia, 2015;Taschner, 2016;Aharonovitz, Vieira, Suyama, 2018;Omoruyi, 2018). To survive the fast-changing business environment, logistics activities are critical business tools to obtaining a competitive advantage.…”
Section: Conclusion and Managerial Implicationmentioning
confidence: 99%
“…This unified measurement of the efficiency and effectiveness is important since it is more informative in identifying the sources of the poor activity performance when compared to simply measuring the efficiency or the effectiveness of the process (Chiou et al, 2010). Other studies which also suggest decomposing the overall performance into its efficiency and effectiveness components include: Karlaftis (2004), , Keh et al (2006), Lan and Lin (2006), Chiou et al (2007), Yu and Lin (2008), Yu (2008), Yu and Lee (2009), Yu and Fan (2009), Hsieh and Lin (2010), Wu et al (2013), Huang et al (2014) and Wong et al (2015).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Poor decision-making by management also leads to disengagement and reduces the organization's revenue (Miles & Clieaf, 2017). Therefore, management's responsibility to find strategic ways to engage employees in the workplace and protect the organization's financial resources (Wong et al, 2015).…”
Section: Disruptive Conflict Behaviors Require Managers Who Implementmentioning
confidence: 99%
“…2016) further stated that e-learning programs are only effective if the employee uses the software and applies what they learned to their job.Financial consequences of disengaged employees Wong, Soh, Chong, and Karia (2015). reported that evidence showed the financial health and viability of firms are directly impacted by employee engagement.…”
mentioning
confidence: 99%